RECONSTRUCTING THE ESSENCE OF METHODS, TOOLS, AND MEDIA IN ISLAMIC EDUCATION IN THE DIGITAL ERA: A TA'DIB AND SPIRITUAL EDUCATION PERSPECTIVE - Ahmad Hikam Mutha’aliin; Abdullah Thalib; Muhammad Luthfi Dzulfikar; Nurhilal Ahmad Fathin Abdurrasyid; Irsad Dulanam (Atta'dib Jurnal Pendidikan Agama Islam, 2026)
Contemporary Islamic education faces a crisis of meaning in the digital era, frequently reducing instructional media and tools into value-neutral, pragmatic instruments and neglecting their spiritual dimensions. This research aims to establish a rigorous ontological demarcation between educational tools and media and to construct an integrative philosophical framework for their use based on Islamic epistemology. This qualitative library research employs a philosophical approach. Data were collected heuristically from academic databases and classical texts, with a focus on the foundational works of Syed Muhammad Naquib Al-Attas and Al-Ghazali. The analysis technique employs hermeneutic interpretation, validated through source triangulation, to systematically dissect the esoteric layers of educational technologies. The findings demonstrate a novel theoretical contribution by proving that while tools are merely functional-technical instruments, digital media act as value-laden, meaning-making environments. Furthermore, this study offers a new integrative paradigm by contextualizing classical Sufi concepts to solve modern digital challenges: translating Al-Ghazali’s mujahadah and riyadhah into digital self-regulation, while operationalizing Al-Attas’s Ta'dib to design media that respect the hierarchy of knowledge. Conclusively, addressing digital disruption requires shifting from mechanical pedagogy to a holistic integration in which digital media serve as esoteric intermediaries, actively guiding students toward moral maturity, adab, and divine consciousness.